2020
DOI: 10.1039/d0se00646g
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a preferentially [001]-oriented Sb2Se3 thin film on diverse substrates and its application in photoelectrochemical water reduction

Abstract: A kinetically controlled growth approach is developed to facilely synthesize preferentially [001]-oriented Sb2Se3 thin-films on diverse substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…158 He also revealed the crystal growth mechanism and charge transport of Sb 2 Se 3 with different orientations. 159 As shown in Fig. 7h1, the randomly-oriented nanoribbons and the nanoribbons vertically aligned to the substrate and electrolyte have a longer diffusion length and, thus, lower charge transport efficiency.…”
Section: Pec Water Splittingmentioning
confidence: 98%
See 1 more Smart Citation
“…158 He also revealed the crystal growth mechanism and charge transport of Sb 2 Se 3 with different orientations. 159 As shown in Fig. 7h1, the randomly-oriented nanoribbons and the nanoribbons vertically aligned to the substrate and electrolyte have a longer diffusion length and, thus, lower charge transport efficiency.…”
Section: Pec Water Splittingmentioning
confidence: 98%
“…(h1) Charge transport of Sb 2 Se 3 with different orientations. (h2) The selenization process and crystal growth mechanism of Sb 2 Se 3 film with [001] texture 159. Copyright 2020 Royal Society of Chemistry.…”
mentioning
confidence: 99%
“…The TC values of the (041), ( 231), (061), and (141) planes are increased after SbCl 3 treatment, meanwhile a reverse trend is observed for the (211) and (221) planes, which may be ascribed to the higher formation energy of (211) and (221) planes. [35][36] In addition, the induction of SbCl 3 treatment may induce the unsaturated atoms (either Sb or Se atoms) at the end of (Sb 4 Se 6 ) n ribbons to bond with the substrate with more perpendicular direction due to the lower surface formation energy of (041), (061), and (141) planes. Wen et al [37] and F. Pattini et al [38] have pointed out that the angle between (Sb 4 Se 6 ) n ribbons and the surface normal of (041), ( 231), ( 061), ( 141), (211), and (221) are 53.4°, 50.8°, 63.6°, 54,2°, 37.3°, and 43.8°, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Their observation indicates that, in the highly [120]-oriented film, the charge transfer from the bottom to the top of the Sb 2 Se 3 film is sluggish because the charges have to hop across the ribbons, in contrast to the [221] oriented case in which charges can efficiently move along the ribbons (Figure d). Zhou et al elucidated the change of the crystallographic orientation of the Sb 2 Se 3 thin films during selenization of sputtered Sb films . They measured XRD and Raman of Sb 2 Se 3 thin films with 15 different selenization times and found that, at the beginning of selenization, amorphous Sb 2 Se 3 forms, followed by the preferred growth along the [001] orientation.…”
Section: Emerging Binary Chalcogenides For Solar Energy Conversionmentioning
confidence: 99%
“…Zhou et al elucidated the change of the crystallographic orientation of the Sb 2 Se 3 thin films during selenization of sputtered Sb films. 140 They measured XRD and Raman of Sb 2 Se 3 thin films with 15 different selenization times and found that, at the beginning of selenization, amorphous Sb 2 Se 3 forms, followed by the preferred growth along the [001] orientation. During the preferential growth period, the texture coefficient of the [001] orientation rapidly increased from 1.9 to 7.1.…”
Section: Strategies Formentioning
confidence: 99%